The essential elements in conducting successfu guidance and counseling at secondary school level: a review - Zvobgo, Ellen Farisayi (Midlands State University, 2015)
This article reviews literature on essential elements in conducting successful guidance and counselling at Secondary school level in Zimbabwe. These elements include; the role of the school counsellor, goals of counselling, qualities of a good counsellor, the knowledge and skills of the counsellor, availability of resources, supervision, workshops and seminars. These factors are crucial for effective implementation of Guidance and Counselling programmes in schools. The paper explores the contribution of each factor to the success of guidance and counselling and acknowledges ideas given by various authorities. Literature reviewed has been drawn from developed and developing countries.